REPRESENTATION OF INHERITANCE RIGHTS IN PATRIARCHAL CULTURE IN BALI BASED ON GENDER EQUALITY THEORY - Dewi, Frisca Putriana; Valentina, Tience Debora (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2025)
Abstract Gender equality is a concept of balance put forward to equalize the position between women and men. In implementing this concept, Balinese people experience challenges in realizing it, this is due to the influence of patriarchal culture. One aspect that is difficult to implement gender equality is inheritance rights in Bali, due to the concept of patriarchal culture that is intertwined with Hindu religious beliefs. The research method used in this research is a literature review with a narrative literature-overview article approach. This research aims to understand a more specific picture of how patriarchal culture influences inheritance rights and how the transformation that occurs to obtain gender equality can be pursued in a complex cultural context such as in Bali. The results of this study show that the patriarchal culture in Bali is influenced by Hinduism and adat, where men are the main heirs through a major inheritance system, while women often experience marginalization and subordination. The results of this study are expected to provide new insights and encourage changes in a more equitable inheritance system. Keywords: Patriarchal Culture; Inheritance Rights; Gender Equality; Balinese Society.Abstrak Kesetaraan gender merupakan suatu konsep keseimbangan yang dikemukakan untuk menyetarakan posisi antara perempuan dan laki-laki. Dalam penerapannya, masyarakat Bali menghadapi tantangan dalam mewujudkan konsep tersebut, yang disebabkan oleh pengaruh budaya patriarki. Salah satu aspek yang sulit diterapkan dalam konteks kesetaraan gender adalah hak waris di Bali, karena konsep budaya patriarki yang melekat erat dengan ajaran agama Hindu. Metode penelitian yang digunakan dalam kajian ini adalah tinjauan pustaka dengan pendekatan artikel naratif-literatur. Penelitian ini bertujuan untuk memahami gambaran yang lebih spesifik mengenai bagaimana budaya patriarki memengaruhi hak waris serta bagaimana transformasi menuju kesetaraan gender dapat diupayakan dalam konteks budaya yang kompleks seperti di Bali. Hasil penelitian menunjukkan bahwa budaya patriarki di Bali dipengaruhi oleh ajaran Hindu dan adat istiadat, di mana laki-laki merupakan ahli waris utama melalui sistem waris utama, sementara perempuan kerap mengalami marginalisasi dan subordinasi. Temuan ini diharapkan dapat memberikan wawasan baru serta mendorong perubahan menuju sistem pewarisan yang lebih adil dan setara. Kata Kunci: Budaya Patriarki; Hak Waris; Kesetaraan Gender; Masyarakat Bali.